Industrial psychology management / edited by Asit K. Ghosh and Prem Kumar - "Ghosh, Asit K. (ed.) ; Kumar, Prem" (New Delhi, 1991)
The Modern Business Enterprise Brings Together A Large Number Of Various Categories Of Workers, Executives And Supervisors Who Interact On A Day-To-Day Basis In The Interests Of The Firm And Their Own Career And Personal Growth. The Subject Of Industrial Psychology That Is The Collective Interaction Based On Individual Abilities And Attitudes Is Of Prime Concern To The Chief Executives Of The Modern Enterprise. The Ways And Means Of Interaction Are As Important As The Concerned Employees Psychological And Behavioural Profiles, Not Only At The Individual Level But Also As Instruments Of Promotion Of Corporate Interests. Human Motivation In A Given Work Situation And The System Of Incentives And Rewards Offered By The Firm Together Constitute The Base Of The Dimensions Of Industrial Psychology In The Present-Day Competitive World.The Book Will Thus Be Of Immense Use To Scholars And Students Of Management, Teachers And Professionals As Well As Practicing Managers.
Keywords: Industrial psychology